Mierle Laderman Ukeles - Seven work ballets - Conte, Kari (Sternberg Press, 2015)
Mierle Laderman Ukeless 1969 manifesto Maintenance Art: Proposal for an Exhibition was a major intervention in feminist performance practices and public art. The proposition argued for the intimate relationship between creative production in the public sphere and domestic labora relationship whose intricacies Ukeles has been unraveling, ever since. Starting in 1977, she became an unsalaried artist-in-residence at the New York City Department of Sanitation, a position that enabled her to introduce radical public art as mainstream culture into an urban system serving and owned by the municipal population. 00Through archival research, this monographic publication focuses on Ukeless work balletsa series of large-scale collaborative performances involving workers, trucks, barges, and hundreds of tons of recyclables which took place between 1983 and 2012 in Givors, Echigo-Tsumari, New York, Pittsburgh, and Rotterdam